Monitoring and analyzing environmental factors favoring outbreaks of Fusarium oxysporum f. sp. vanillae in a vanilla shade house - Bautista Hernández, Antonio; Ramos Quintana, Fernando; Sotelo Nava, Héctor (International Journal of Agricultural and Biological Engineering, 2018)
This paper presents a study of relationships between climatic factors favoring outbreaks of the Fusarium oxysporum f. sp. vanillae (FOV) within a shade-house installed at the Veracruz State, México. The relationship between temperature (T) and relative humidity (RH) within four predefined specific zones inside the shade-house were mainly studied and analyzed by using compiled data from 2010 to 2014 during different periods of the year. T and RH sensors were installed in such specific zones to determine the difference of the behavior of both parameters during particular periods of the year. Derived from the analyses of the compiled data and from reported literature, a set of rules were built to express ranges of T and RH that favor the fungus outbreaks. Such rules were represented quantitatively and qualitatively to facilitate their interpretation. Quantitative data were transformed into qualitative data using a fuzzy logic approach. The results showed important relationships between the behavior of T and RH with FOV outbreaks depending on different zones of the shade house and on particular periods of the year. Most of the occurrences of FOV were detected within the zones that showed lower temperatures and higher relative humidity (zones Z3 and Z4), where most of the sanitation actions occurred (70%). Zone Z1 was the one with higher temperature and lower relative humidity, which resulted with less occurrences of fungus outbreaks. It was recommended to monitor the variables T/RH in different zones inside the new shade houses to be built and avoid enclosing the shade-house by hills that could block the sunlight and produce runoffs of water, thus contributing to increase the humidity of the installation. Keywords: vanilla, shade house, greenhouse, monitoring, environmental factor, Fusarium oxysporum f.sp. vanillae, fungus, fuzzy sets DOI: 10.25165/j.ijabe.20181101.2803 Citation: Hernández A B, Quintana F R, Nava H S. Monitoring and analyzing environmental factors favoring outbreaks of Fusarium oxysporum f.sp.vanillae in a vanilla shade house. Int J Agric & Biol Eng, 2018; 11(1): 58–65.